How to ditch your fairy - Larbalestier, Justine (New York : Scholastic Inc, 2010)
In a world in which everyone has a personal fairy who tends to one aspect of daily life, fourteen-year-old Charlie decides she does not want hers--a parking fairy--and embarks on a series of misadventures designed to rid herself of the invisible sprite and replace it with a better one, like her friend Rochelle's shopping fairy.
Publisher's Weekly
School Library Journal
Wilson's Junior High School
Bulletin (Center for Children's books), November 2008
Horn Book, April 2009
Kirkus Review, August 2008
Keywords: Fairies -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Magic -- Juvenile fiction; Fairies -- Fiction; Interpersonal relations -- Fiction; Magic -- Fiction; Fairies -- Fiction; Interpersonal relations -- Fiction; Magic -- Fiction